2021
DOI: 10.1016/j.sjbs.2021.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of gallic acid as skeletal muscle relaxant in animal experimental models

Abstract: Background and Objective Many natural bioactive chemicals have been shown to have functional activity, suggesting that they could be useful in the treatment and management of a wide range of chronic conditions. Flavonoids, which include gallic acid (GA), are the most abundant polyphenols found in nature. Skeletal muscle relaxants are drugs that reduce undesired spasms while maintaining awareness and reflexes unaffected. The purpose of this investigation was to determine if GA has any skeletal musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Gallic acid is one of the most abundant polyphenols identified in nature [ 251 , 252 ]. Behera et al [ 253 ] reported that gallic acid reveals antioxidant or free radical scavengers in adipocyte proliferation.…”
Section: Hydroxybenzoic Acids (Gallic Acid and Protocatechuic Acid)mentioning
confidence: 99%
“…Gallic acid is one of the most abundant polyphenols identified in nature [ 251 , 252 ]. Behera et al [ 253 ] reported that gallic acid reveals antioxidant or free radical scavengers in adipocyte proliferation.…”
Section: Hydroxybenzoic Acids (Gallic Acid and Protocatechuic Acid)mentioning
confidence: 99%
“…It has anti-inflammatory and antibacterial activities (Li et al, 2017). Gallic acid was effective as a skeletal muscle relaxant in experimental animal models (Asdaq et al, 2021). The antiinflammatory activity of gallic acid was evaluated in human gestational tissues.…”
Section: Introductionmentioning
confidence: 99%